Daya Antibakteri Ekstrak Kulit Buah Kakao (Theobroma cacao L.) sebagai Alternatif Bahan Irigasi Saluran Akar terhadap Streptococcus viridans - Yola Widya Putri Damania; Dwi Warna Aju Fatmawati; Dyah Setyorini (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Streptococcus viridans is a Gram-positive facultative anaerobe that most commonly found in infected root canals. The biomechanical preparation of root canal treatment requires root canal irrigation as it functions not only used to cleanser but also antibacterial agent. NaOCl 2,5% is the most commonly used Endodontic irrigant, however it is still considered to have several disadvantages. Cocoa pod shell (Theobroma cacao L.) are industrial plantation waste which has a source of antibacterial compounds that expected to be an alternative to substitute NaOCl’s drawbacks. This study aim to examine the antibacterial effectiveness of cocoa pod shell extract against S.viridans. The research is posttest only group control design and the method use broth dilution to examine the antibacterial effectiveness. The results of Kolmogorov-Smirnov test and Levene's test showed that data set which exhibited both non-normally distributed and non-homogeneous, continued with the nonparametric test using the Kruskal-wallis test, it was found that p <0.5 meant there were significantly differences between all study groups. 25%; 12,5%; 6,25%; 3,125%; 1,56%; 0,78% concentration of cocoa pod shell extract has antibacterial activity against S.viridans. The Minimum Inhibitory Concentration to against S.viridans is cocoa pod shell extract concentration 0,78%. Cocoa pod shell extract concentration 12,5% and 25% equal to NaOCL 2,5%.